ANALYSIS OF STUDENT RESPONSE TO THE IMPLEMENTATION OF THE ETHNO-FLIPPED CLASSROOM MODEL ASSISTED BY COLLABORATIVE CLOUD CLASSROOM - Ramadhani, Rahmi; Napitupulu, E. Elvis; Sitompul, Pardomuan (Jurnal Pendidikan Matematika (JUPITEK), 2023)
The ethno-flipped classroom model is a collaborative and student-centered learning model developed by integrating the flipped learning model and the ethnomathematics approach. The implementation of the ethno-flipped classroom model is assisted by Collaborative Cloud Classroom which was developed as a Learning Management System during the implementation of learning. The purpose of this study was to determine student responses to the application of the ethno-flipped classroom model assisted by Collaborative Cloud Classroom for high school students in Gunungsitoli City, Nias Island, North Sumatra Province. This research is descriptive quantitative research with data collection techniques using Likert-scale questionnaires in Small Group and Field Test. The research sample was Gunungsitoli City High School students, namely 25 students in the small group stage and 222 students in the filed test stage. The results showed that 83% of students gave a very good response at the small group stage and 85% of students gave a very good response to the application of the model at the filed test stage. The achievement of the percentage of student responses concluded that the ethno-flipped classroom model assisted by Collaborative Cloud Classroom can be further implemented in the application of other cultural contexts in future research